2020
DOI: 10.1093/europace/euaa126
|View full text |Cite
|
Sign up to set email alerts
|

Prescription of oral anticoagulants and antiplatelets for stroke prophylaxis in atrial fibrillation: nationwide time series ecological analysis

Abstract: Aims To investigate trends in the prescription of oral anticoagulants (OACs) and antiplatelet agents for atrial fibrillation (AF). Methods and results Prescription data for 450 518 patients with AF from 3352 General Practices in England, was obtained from the GRASP-AF registry, 2009–2018. Annualized temporal trends for OAC and antiplatelet prescription were reported according to eligibility based on stroke risk (CHADS2 or CHA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 26 publications
1
14
0
1
Order By: Relevance
“…2,12,13 Data from the EURObservational Research Programme in AF (EORP-AF) found that adherence to guideline-recommended therapies in the treatment of AF is associated with lower mortality, 14 yet large variability persists in the delivery of such therapies across Europe. 15,16 To improve the implementation of evidence-based medicine, 17 some professional organizations have developed quality standards, clinical indicators, and quality measures to evaluate and improve the quality of AF care. [18][19][20][21][22] However, no AF quality indicators (QIs) have been specifically designed for the wider international community.…”
Section: Introductionmentioning
confidence: 99%
“…2,12,13 Data from the EURObservational Research Programme in AF (EORP-AF) found that adherence to guideline-recommended therapies in the treatment of AF is associated with lower mortality, 14 yet large variability persists in the delivery of such therapies across Europe. 15,16 To improve the implementation of evidence-based medicine, 17 some professional organizations have developed quality standards, clinical indicators, and quality measures to evaluate and improve the quality of AF care. [18][19][20][21][22] However, no AF quality indicators (QIs) have been specifically designed for the wider international community.…”
Section: Introductionmentioning
confidence: 99%
“…In the PINNACLE Registry, 31.3% of patients without risk factors in CHA 2 DS 2--VASc score received OACs [15]. The GRASP-AF Registry showed that from 2009 to 2018, the percentage of patients with low thromboembolic risk receiving OACs was 36.2-46.4% [16]. In PREFER in AF, more than half of AF patients at low and intermediate thromboembolic risk received OACs: 70.1% of the patients with CHA 2 DS 2 -VASc score 1 and 62.5% of patients without any CHA 2 DS 2 -VASc stroke risk factor [17].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the presented study, AF type or impaired kidney function were not shown to be the predictors of OAC use in patients at low thromboembolic risk. It has been reported that the aforementioned factors increase the risk of thromboembolic complications in patients with AF or predispose them to thrombus formation in the left atrial appendage [8][9][10][11][12][13][14][15][16][17][18][19][20]. Study results connected with anticoagulant overtreatment of patients with AF prove that it is common and most likely stems from using OACs due to temporary indications to anticoagulant therapy and from the presence of thromboembolic risk factors not included in the CHA 2 DS 2 -VASc score.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, there were between 355,138 and 1,442,792 fewer tests (depending on the measure) conducted by the end of September 2020 compared with the previous years. No such recovery was observed for INR testing, possibly due to many patients being switched from warfarin (which requires INR monitoring) to direct oral anticoagulants (which do not), which had been occurring prior to the pandemic 20 , but which was accelerated to avoid unnecessary patient contact with primary care during the pandemic. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, INR testing was already in decline from 2018-2019 and this was amplified at the start of lockdown, presumably due to an acceleration of switching patients from warfarin to direct oral anticoagulants that do not require regular blood test monitoring. 20,21…”
Section: Discussionmentioning
confidence: 99%